4=3u-44+u-98

Rewrite the equation as 3u-44+u-98=4.

3u-44+u-98=4

To write 3u-44 as a fraction with a common denominator, multiply by 22.

3u-44⋅22+u-98=4

Write each expression with a common denominator of 8, by multiplying each by an appropriate factor of 1.

Multiply 3u-44 and 22.

(3u-4)⋅24⋅2+u-98=4

Multiply 4 by 2.

(3u-4)⋅28+u-98=4

(3u-4)⋅28+u-98=4

Combine the numerators over the common denominator.

(3u-4)⋅2+u-98=4

Reorder terms.

u+2(3u-4)-98=4

Rewrite u+2(3u-4)-98 in a factored form.

Apply the distributive property.

u+2(3u)+2⋅-4-98=4

Multiply 3 by 2.

u+6u+2⋅-4-98=4

Multiply 2 by -4.

u+6u-8-98=4

Add u and 6u.

7u-8-98=4

Subtract 9 from -8.

7u-178=4

7u-178=4

7u-178=4

Multiply both sides of the equation by 8.

7u-17=4⋅(8)

Remove parentheses.

7u-17=4⋅(8)

Multiply 4 by 8.

7u-17=32

Move all terms not containing u to the right side of the equation.

Add 17 to both sides of the equation.

7u=32+17

Add 32 and 17.

7u=49

7u=49

Divide each term by 7 and simplify.

Divide each term in 7u=49 by 7.

7u7=497

Cancel the common factor of 7.

Cancel the common factor.

7u7=497

Divide u by 1.

u=497

u=497

Divide 49 by 7.

u=7

u=7

u=7

Solve for u 4=(3u-4)/4+(u-9)/8